Structuring the Potential Losses from Vandalism; Actions of Insurers Confronted with the Insecurity Resulting from Vandalism - Guelton, Sonia (International Journal of Criminology and Sociology, 2016)
Social disturbances have occurred repeatedly in recent years in several countries. The number of incivilities is important from a social point of view as long as they often concern fragile populations, the poorest, and small shops and businesses. In the meantime, there are concentrated in deprived areas where it is all the most important to prevent exclusion and desertification. The risk connected with vandalism is a risk of social exclusion and economic division for the territories. The article tries to characterize the spatial concentration of crime. It questions the action of insurances in the reduction of spatial discrepancies and social injustice.